Coerção, manipulação e tecnologia: estratégias de monetização em jogos free-to-play. - Oliveira, Jônatas Kerr (2022)
Starting from the discomfort of many involved in the videogame market with the new monetization practices present in the emergence of the free-to-play model, I investigate this business model and propose an approach to identify coercive or manipulative potential in digital games directly from the game as a technological artifact. This is a different perspective from previous approaches (mainly game design dark patterns), which speculated about the original intention of the designer, in some cases leading to wrong conclusions, and which erroneously pointed to some game patterns intrinsic to the free-to-play model as naturally coercive. An approach based on the analysis of the artifact and not on speculation about the developer's intention is especially relevant, because in the context of imitation, a common market practice, a design with manipulative or coercive potential can be implemented without proper awareness of its operation, leading to a dissonance between original and derived intentionality. Applying the proposed approach in case studies, and focusing on F2P games for mobile devices, it was possible to identify several design elements with manipulative or coercive potential at all stages of the “Acquisition – Retention – Conversion” process. However, this does not necessarily mean that all free-to-play games use coercive or manipulative strategies, since two games can implement the same design pattern, where one of them has coercive or manipulative potential and the other does not, showing in practice that the coercive potential is in the contextualization layer, through design cues, not in design patterns, as much of the bibliography suggests. With the proposed approach, designers can investigate their own designs in search of elements with coercive or manipulative potential, breaking the cycle of imitation and allowing a reflection on game making and its implications for the society